Vasiliy Zinchenko (13.07.1943 – 23.04.2017). In Memoriam - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):187.